Kajian Akademis Tata Kelola dan Manajemen Sumber Daya Buatan: Teknologi Siber dan Infrastruktur Digital sebagai Obyek Vital Nasional dalam Kerangka Undang-Undang Nomor 23 Tahun 2019 tentang Pengelolaan Sumber Daya Nasional untuk Pertahanan Negara - Wujarso, Riyanto; Surjaatmadja, Surachman; Wahyudi, Imam Tri (Lembaga Teewan Journal Solutions, 2026)
The shift of the state's center of gravity into the digital domain has created new vulnerabilities, where disruptions to cyber infrastructure may lead to national paralysis. This study examines the governance of cyber technology and digital infrastructure as National Vital Objects within the framework of Law No. 23 of 2019 on the Management of National Resources for State Defense (UU PSDN). A systems thinking approach was employed using Causal Loop Diagrams (CLD) and SWOT/TOWS analysis to identify the institutional factors underlying the gap between high cyber threat intensity and weak compliance enforcement. The findings reveal that cyber technology and digital infrastructure conceptually and operationally qualify as Artificial Resources and National Vital Objects but lack legal certainty due to the absence of the Government Regulation mandated by Article 56 of the UU PSDN. This regulatory gap weakens the implementation of Article 59 on asset maintenance and reduces the effectiveness of cyber detection and response mechanisms. The TOWS analysis positions Indonesia in a turn-around strategic posture emphasizing internal institutional consolidation. The study recommends accelerating the issuance of the Government Regulation, harmonizing it with Presidential Regulation No. 82 of 2022, establishing mandatory incident reporting and administrative sanctions, allocating a minimum cybersecurity budget, expediting the Cyber Security and Resilience Bill, and institutionalizing a Cyber Reserve Component through professional partnerships.